IoT-based noise measuring tool with FC-04 sound sensor for polyurethane dampening materials - Vicha Indriany; Masthura Masthura; Nazaruddin Nasution (Indonesian Physics Communication, 2024)
Increased noise caused by human and industrial activities can cause health problems, such as stress, affecting sleep quality, and having negative effects on long-term health, usually such as hearing problems, high blood pressure, and depression. This study aims to make a noise-measuring instrument, examine the comparison of the results of sound intensity level measurements, and examine the damping ability of polyurethane. The sensor used in this study is the FC-04 sound sensor which functions as a sound intensity level meter that works by changing the sound scale to an electrical quantity. The data that has been obtained is a comparison of the measurement results using the factory standard sound level meter (SLM) and an artificial noise measuring instrument which is analyzed using the calculation of the percent deviation. As for the measurement data of the damper material polyurethane before and after, analyzed using reduction effectiveness calculations. The results of measuring the sound intensity level using the factory standard SLM and an artificial noise meter obtained an average value of the sound intensity level of 72.67 dB and 67.77 dB. From the results of the two measuring instruments, the percentage deviation of the measuring instrument is 6.7% with minimum and maximum percentage deviation values of 3.1% and 11.7%. The results of the measurement of the reduction effectiveness value of the damper material polyurethane using factory standard SLM and artificial noise measurement tools of 14.7% and 14.8%.